PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI NEGARAKU INDONESIA DI KELAS IV SD ISLAM PLUS YLPI RIAU - Duta Dwi Ananda; Zaka Hadikusuma Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to produce animated video-based learning media on Negaraku Indonesia material in class IV of SD Islam Plus YLPI. This research uses qualitative and quantitative methods. This research is development research (Research and Development) where the development uses a 4D model (Define, Design, Development, Dissemination). Validation of the animated video media developed was carried out by 6 validators in 3 aspects, namely media/design aspects, language aspects, and material aspects. In media/design aspect validation, an assessment score of 91.9% or very valid was obtained. Furthermore, in the language aspect, an assessment score of 96% or very valid was obtained. And in the material aspect, an assessment score of 92.5% was obtained. The average score obtained from the animated video media developed was 93.4% in the very valid category. The average score obtained from students' responses to animated video media in the material Negaraku Indonesia in class IV SD Islam Plus YLPI Riau is 83.2% or very valid.